2015
DOI: 10.1007/s10566-015-9343-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bullying and Victimization on Cognitive Empathy Development During the Transition to Middle School

Abstract: Background Interventions aimed at reducing bullying behavior commonly target the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 47 publications
0
28
0
6
Order By: Relevance
“…The study suggested that the inclusion of social pedagogy in the professional education and training of pedagogic and care professionals might usefully help students to adopt a social pedagogic approach to prevent and tackle bullying in schools. Williford, Boulton, & et al (2016) examined the naturally-occurring changes in cognitive empathy during the transition from elementary to middle school. It also explored the effect of bullying and victimization involvement on changes in cognitive empathy over time, and specifically during this school transition.…”
Section: Related Studiesmentioning
confidence: 99%
“…The study suggested that the inclusion of social pedagogy in the professional education and training of pedagogic and care professionals might usefully help students to adopt a social pedagogic approach to prevent and tackle bullying in schools. Williford, Boulton, & et al (2016) examined the naturally-occurring changes in cognitive empathy during the transition from elementary to middle school. It also explored the effect of bullying and victimization involvement on changes in cognitive empathy over time, and specifically during this school transition.…”
Section: Related Studiesmentioning
confidence: 99%
“…Savage & Tokunaga (2017) argued that bullies might look impressive and confi dent, but a lot of them found out their confi dence or released the internal anxiety by bullying and controlling others. Williford et al (2016) indicated that many bullies and victims showed bad academic performance at school to relatively appear low self-evaluation. Moreover, a lot of bullies and victims felt hopeless due to negative experience of worse interaction with external systems, unhealthy family structure, alienated peer relationship, and bad interaction with teachers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Así, en el caso de los trastornos del neurodesarrollo (trastorno por déficit de atención e hiperactividad o trastorno del espectro autista), el centro escolar tiene constancia de estos casos ya que, generalmente, han sido diagnosticados por los orientadores en la EP y en el cambio de etapa se informa de las adaptaciones curriculares adecuadas que permiten dar una respuesta educativa más ajustada a las características de estos estudiantes. Sin embargo, en el caso de los trastornos de la ansiedad y depresivos, el diagnóstico se realiza en el ámbito sanitario y, por tanto, el ámbito educativo puede desconocer estas situaciones Mala imagen de sí mismo (Folgar et al, 2013) Bajo nivel de autoestima (Coelho et al, 2017;Ryan, Shim y Makara, 2013) Bajo nivel de empatía (Williford et al, 2016;Williford, Boulton y Jenson, 2014) Bajo nivel de inteligencia emocional (Adeyemo, 2002) Interinestabilidad del individuo (Vanlede, Little y Card, 2006) Problemas de autorregulación (Pears, Kim y Leve, 2012;Rudolph et al, 2001) Baja motivación (Madjar, Cohen y Shoval, 2018;Monarca et al, 2012) Bajo nivel de autoeficacia (Madjar y Chohat, 2016) Preocupación ( Padres divorciados (Hines y Mack, 2007;Langberg et al, 2008) Ambiente familiar Que los padres dejen de ser un referente principal durante la transición (Folgar et al, 2013) Padres que agreden a sus hijos (Yaros et al, 2016) Escaso contacto padres-profesorado (Crosnoe, 2009;Edwards et al, 2014) Tener apego hacia los padres (Duchesne, Ratelle, Poitras y Drouin, 2009)…”
Section: Génerounclassified